PELATIHAN DAN PENDAMPINGAN PENGEMBANGAN MATERI PENDIDIKAN PANCASILA PADA ELEMEN PANCASILA DAN UUD NRI TAHUN 1945 BERORIENTASI TPACK - Hartanto, Rima Vien Permata; Triyanto; Ariana, Yudi; Gunawati, Dewi; Rejekiningsih, Triana; Noventari, Widya (Education and Talent Development Center of Indonesia, 2025)
Pancasila Education subject teachers have an important position in the learning process, because the teacher is one of the seven components of teaching which includes teachers, students, methods, models, curriculum, facilities and infrastructure and evaluation in learning. One of the competencies that Pancasila Education subject teachers must have is the competence to develop learning materials, which is the process of organising materials, which have been arranged systematically that teachers can use in the learning process. However, based on the results of a questionnaire to junior high school Pancasila Education teachers in Grobogan Regency, it was found that teachers have limited ability to develop materials on the elements of Pancasila, the 1945 Constitution of the Republic of Indonesia and understanding of learning materials related to law oriented Technological Pedagogical Content Knowledge (TPACK). For this reason, it is necessary to have training and assistance in developing Pancasila Education materials for junior high school / MTs at the Pancasila Element and the 1945 Constitution oriented to Technological Pedagogical Content Knowledge (TPACK). Specifically, this Community Service aims to improve the ability of teachers in developing materials on the elements of Pancasila and the 1945 Constitution of the Republic of Indonesia and mastery of legal materials to improve professionalism and support the learning process of Pancasila Education. The final result of this activity is to produce Pancasila Education teachers who have the ability to master the subject matter broadly and deeply in accordance with the professional competence of teachers based on Law Number 14 of 2005 concerning Teachers and Lecturers.